Analisis Pengaruh Capital Adequacy Ratio (CAR), NonPerforming Loan (NPL) dan Loan to Deposit Rasio (LDR) Terhadap Return on Equity (ROE) pada Perbankan yang Terdaftar di LQ45 - Gusmawarni, Gusmawarni; Nurulrahmatiah, Nafisah; Muthiah, Hanifa (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to determine and analyze the influence of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Return On Equity (ROE) in banks registered in LQ45. Type of associative research with primary data in and sourced from research instruments. The research instrument used is a list of tables in the form of financial reports consisting of balance sheet data in the form of capital, RWA, non-performing loans. credit provided, third party funds, net profit and equity. The population in this research is all banks registered in LQ45, namely 7 banks. The sample in this research is 5 banks registered in LQ45 from 2018-2022. The sampling technique used is purposive sampling. The criteria for banks listed on LQ45 are as follows: Companies listed on the Indonesia Stock Exchange in 2017 and companies that experienced an increase in RWA. Data collection in this research used documentation and literature study. The data that has been collected will be analyzed using the classical assumption test, multiple linear regression, multiple correlation coefficient, determination test, t test and f test. The research results show that the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) simultaneously have a significant effect on Return On Equity (ROE) in banks registered in LQ45.